การศึกษาความเป็นไปได้ทางการเงินของการขยายการลงทุนโรงสีข้าว: กรณีศึกษากลุ่มวิสาหกิจชุมชนศูนย์ข้าวชุมชนตำบลไร่มะขาม อำเภอบ้านลาด จังหวัดเพชรบุรี - สิริโรจนพุฒิ, วิไลวรรณ; ศศิวิมลฤทธิ์, กนกกาญจน์; ธนาวิวัฒน์, ณัฐปคัลภ์ (Journal of Applied Economics and Management Strategy, 2018)
The objective of this research was to study the financial feasibility of the investment in comprehensive and incomprehensive rice mills (hereafter called CRM and ICRM respectively) in a Rai Makham community enterprise, Ban Lat district, Phetchaburi province, Thailand. The data were collected from in-depth interviews with the members of a Rai Makham community enterprise. In order to evaluate the financial feasibility, the relevant measurements, i.e., discounted payback period (DPB), net present value (NPV), benefit cost ratio (BCR), internal rate of return (IRR), and switching value test (SVT), were adopted for this study. The financial feasibility analysis of the rice mill investments in ICRM and CRM were then compared. Regarding the first case of the investment in the ICRM, the initial investment was allocated for rice mill construction and a milling machine. During the production process, milling and packing were conducted on site, but the drying and color sorting processes were operated by outsourced mills. Regarding the second case of investment in the CRM, the initial investment was in rice mill construction, milling machinery, a paddy dryer, and a color sorting machine. All of the production processes in the second case were conducted solely by the mill itself. To analyze the financial feasibility of the investment in the ICRM (case 1), it was found to be financially feasible since the net present value (NPV) was positive with a value of 3,119,315.30 baht. The discounted payback period (DPB) was 6 years 10 months and 15 days. The benefit-cost ratio (BCR) was 1.07. The internal of return (IRR) was 15.97%. The switching value test benefit (SVTB) was 6.28%, and the switching value test cost (SVTC) was 6.70%. In addition, the financial feasibility analysis of the investment in the CRM (case 2) also indicated financially feasibility. The NPV was positive, with the value of 25,033,331.27 baht. The DPB was 3 years 5 months and 1 day. The BCR was 1.37. IRR was 32.83%. SVTB was 27.14%, and the SVTC was 37.26%. The comparison between the two cases revealed that the investment in the CRM should be carried out for further benefits because a greater NPV during the final year of the project, as well as higher BCR and IRR rather than those of the investment of ICRM, were evident. Moreover, the DPB of the investment in the CRM was shorter than that in the ICRM, and the benefit risk and cost risk of the investment in the CRM were lower than the investment in the ICRM. Keywords: Financial Feasibility, Rice Mill, Community Enterprise